Gesamtkunstwerk - A obra de arte total - de Richard Wagner (1813-1883) e a criação da imagem simbólica no drama O Anel do Nibelungo - Silva, Allan Lourenço da (2024)
This doctoral thesis presents the results of my research developed in the doctoral course of the Postgraduate Program in Cultural Performances, Interdisciplinary Area of the Faculty of Social Sciences of the Federal University of Goiás. The general objective was to understand the process of materialization/concretion of conception of Gesamtkunstwerk as an aesthetic phenomenon in the drama The Ring of the Nibelung, produced by Richard Wagner, in 1876, in Bayreuth, Germany. The core of the research lies in the following question: in what way the production of Gesamtkunstwerk – concept of Total Work of Art – manifested itself as a phenomenon in the creation of the symbolic image in the work of Richard Wagner and in his proposal for operatic aesthetic reform, consolidating it. whether in the drama? I used an exploratory methodology, dedicating myself to reading and analyzing theses, articles, books, magazines, newspapers and images, in order to find pertinent materials that could elucidate the process of creating Gesamtkunstwerk in the drama The Ring of the Nibelung. I started from the hypothesis that Richard Wagner's Gesamtkunstwerk materializes in drama. It is through the elaboration of the drama that its proposal is configured as a concrete aesthetic phenomenon. Thus, I sought to broaden the understanding of the creation of the symbolic image in drama, exploring its poetic and dramatic potentials, based on the Wagnerian conception of Gesamtkunstwerk. The research carried out allowed me to conclude that the image, in Wagner, is not dissociated from time and space, nor is it restricted to the field of ideas; it presents itself in a tangible/concrete way. According to the thesis, Richard Wagner, when conceiving Gesamtkunstwerk, sought to develop it through the creation of an image that materializes in and as drama.